2020
DOI: 10.3390/ijms21134600
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel microRNA Profiles Dysregulated in Plasma and Tissue of Abdominal Aortic Aneurysm Patients

Abstract: microRNAs (miRNAs) are small RNAs that regulate different biological processes. Our objective was to identify miRNAs dysregulated in plasma and tissue of patients with abdominal aortic aneurysm (AAA) and explore new potential targets involved in AAA. Fifty-seven subjects were recruited for a plasma study (30 AAA patients, 16 healthy volunteers and 11 patients with atherosclerosis). The expression level of 179 miRNAs was screened in plasma from a subset of samples, and dysregulated miRNAs were validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…When comparing data on patients with PA with our previously published article on AAA patients, 7 we can observe that eight of the 14 miRs were changed in different ways in the subgroups of patients with PA. Six of the 14 miRs (miR-33a, miR-103a, miR-125a, miR-192, miR-215, and miR-451) were altered in patients with PA with concomitant AAA. Among the miRs, miR-103a has previously been identified among AAA patients in a study by Plana et al, 13 as being downregulated 1.4-fold in plasma of AAA patients when unadjusted for covariates and upregulated 1.3-fold in aortic tissue from AAA patients. This miR was slightly upregulated in plasma from AAA patients in our previous study.…”
Section: Discussionmentioning
confidence: 95%
“…When comparing data on patients with PA with our previously published article on AAA patients, 7 we can observe that eight of the 14 miRs were changed in different ways in the subgroups of patients with PA. Six of the 14 miRs (miR-33a, miR-103a, miR-125a, miR-192, miR-215, and miR-451) were altered in patients with PA with concomitant AAA. Among the miRs, miR-103a has previously been identified among AAA patients in a study by Plana et al, 13 as being downregulated 1.4-fold in plasma of AAA patients when unadjusted for covariates and upregulated 1.3-fold in aortic tissue from AAA patients. This miR was slightly upregulated in plasma from AAA patients in our previous study.…”
Section: Discussionmentioning
confidence: 95%
“… 61 Another study also confirmed that THBS2 expression was increased in abdominal aortic aneurysm tissue, and further found that THBS2 could act as a potential target of miR-195-5p , which may be involved in the formation of abdominal aortic aneurysm. 55 We found that THBS2 was highly expressed in the tissues of IA. This is similar to the results of the various previous studies, which prove that THBS2 may be involved in the formation of aneurysms, but the specific mechanism needs to be further studied.…”
Section: Discussionmentioning
confidence: 74%
“…THBS2 is a multifunctional stromal cell protein encoded by the THBS2 gene and belongs to the thrombinsensitive protein family. 55 It has been reported to be involved in the regulation of angiogenesis, proliferation, apoptosis, tumor migration, autophagy and transforming growth factor (TGF) β activation. [56][57][58][59] In arteries, THBS2 is mainly secreted by the smooth muscle cells and partly by endothelial cells.…”
Section: Dovepressmentioning
confidence: 99%
“…Multiple types of PVADSCs can be induced by the transfection of microRNA (miRNA) mimics ( 72 ). Based on gene set enrichment analysis, the respective expression levels of miR-27b-3p and miR-221-3p in plasma were 1.6-fold and 1.9-fold higher in patients with AAAs than in healthy controls ( 73 ). Additionally, miR-221-3p is highly expressed in obese PVAT-derived extracellular vesicles (EVs).…”
Section: Cellular and Molecular Contact Between Dysfunctional Pvat And Aaa Pathologymentioning
confidence: 99%